The influence of the inheritance on the occurrence of hypodontia and hyperdontia in children in the Federation of Bosnia and Herzegovina - Dizdarević-Spahić Mervana (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Purpose: The purpose of the research was to establish and mutually complement the frequency of hypodontia and hyperdontia in selected locations of Bosnia and Herzegovina, and to assess the participation of hereditary factors in the registered heterogeneity. Respondents and Procedures: A sample of 1,640 children of school age, both sexes, aged 12-14, served as the subject of research. The sample was collected from five urban centers in the Federation of Bosnia and Herzegovina: Sarajevo, Mostar, Tuzla, Bihać and Gorazde. In order to estimate the difference in the number of respondents by sex, as well as in assessing the differences in the frequency of observed anomalies (hyperdontia and hypodontia), a ch 2 test with a statistical significance limit p <0.05 was applied. The Fisher Exact Test was used to assess the correlation between the occurrence of hyperdontia and hypodontia between children and parents. Scientifically verified ver. Ver. MedCalc 11.5.0.0. In order to evaluate the distinction between possible hereditary and non-positive factors, an assessment of heritability was performed (h) by applying regression analysis (parent-offspring regression). Results: A total of 40 children with anomalies of the number of teeth were identified, of which 16 boys and 24 girls. There was no statistically significant difference in the frequency of hypodontia and hyperdontia between boys and girls with respect to geographic regions (ch 2 = 0.500; P = 0.9735). Conclusion: The total prevalence of hypodontia and hyperdontia was 2.43. The prevalence of hypodontia is 1.58, and the hyperdontia is 0.85. The relative risk of anomalies in the number of teeth in children is 8,965 and is statistically significant, indicating that the likelihood of the occurrence of this disorder in children whose at least one parent has the same anomaly is greater.